Spiritual Well-Being and Death Anxiety in Chronic Diseases: A Meta-Analysis Study - Putri, Oktariana Hanggoro; Anganthi, Nisa Rachmah Nur (Universitas Muhammadiyah Surakarta, 2023)
Abstract. Death anxiety is the most common psychiatric consequence experienced by people with chronic diseases. A potentially important factor in reducing death anxiety is spiritual well-being. There are many studies linking spiritual well-being and death anxiety, but some results show differences. This study aims to summarize various research results related to the relationship between spiritual well-being and death anxiety in patients with chronic disease to obtain a combined effect size. The research design uses meta-analysis to get a summary of the effect size from research on the relationship between spiritual well-being and death anxiety in people with chronic diseases. Sources of information were collected through Publication in Sage Journal, PubMed, ProQuest, Springer LINK, Science Direct, and Google Scholar. Inclusive criteria were the articles from 2011 until 2021, the publication is done in English, the participants are at least 18 years old, report sufficient statistical data for quantitative synthesis, and the existence of measuring instrument information from the two variables. The findings show that a total of eight studies and nine effect sizes met the inclusive criteria. The protocol for reporting the results of meta-analyses is PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The results of the analysis show that the relationship between spiritual well-being and death anxiety is -0.26; 95% CI; with a range of -0.40 to -0.11. The quality of all evidence was evaluated using GRADE (Grading of Recommendations Assessment, Development, and Evaluation), the results were in the moderate category. This meta-analysis found a negative relationship between spiritual well-being and death anxiety in people with chronic diseases with a low effect size. The conclusion of the study shows that spiritual well-being can be a variable for reducing death anxiety in people with chronic disease. The research implications show that there is an urgency for health professionals in managing patients with chronic diseases to pay more attention to their spiritual well-being.Keywords: chronic disease; death anxiety; spiritual well-being